Protective effects of carvacrol against diabetes-induced reproductive damage in male rats: Modulation of Nrf2/HO-1 signalling pathway and inhibition of Nf-kB-mediated testicular apoptosis and inflammation - Arkali, Gozde; Aksakal, Mesut; Kaya, Seyma Ozer (Wiley, 2021)
Diabetes mellitus, which causes many complications, also adversely affects reproductive system in men. Studies reported that natural antioxidants are effective in reducing important complication risks caused by diabetes. Carvacrol is an antioxidant phenolic monoterpene compound with therapeutic effect in various diseases found in essential oils of aromatic plants such as pepper, wild bergamot and thyme. We aimed to investigate the effects of carvacrol on diabetes-induced reproductive damage in male rats by evaluating the Nrf2/HO-1 pathway and Nf-kB-mediated apoptosis/inflammation and spermatological parameters. For this purpose, 74 Wistar albino male rats were used. The diabetes model was performed using single-dose intraperitoneal injection of streptozotocin 55 mg/kg. Rats were fed with carvacrol 75 mg/kg/daily/gavage for 4 and 8 weeks. Rats were divided into four groups: control group, diabetic group, carvacrol group which fed with carvacrol and the diabetic group which fed with carvacrol. It was determined that carvacrol significantly decreased malondialdehyde levels, Bax,COX-2,Nf-kB protein expression levels, Bax/Bcl-2 ratio and significantly increased glutathione peroxidase, catalase activities, Bcl-2, Nrf2,HO-1 protein expression levels and it was determined that had a positive effect on spermatological parameters. In conclusion, the negative effects of diabetes in the male reproductive system can be prevented and/or reduced by giving carvacrol.
Keywords: carvacrol; diabetes; Nf-kB-mediated apoptosis; Nrf2/HO-1; sperm quality